If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3x + -5.04 = -6.3 Reorder the terms: -5.04 + 0.3x = -6.3 Solving -5.04 + 0.3x = -6.3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5.04' to each side of the equation. -5.04 + 5.04 + 0.3x = -6.3 + 5.04 Combine like terms: -5.04 + 5.04 = 0.00 0.00 + 0.3x = -6.3 + 5.04 0.3x = -6.3 + 5.04 Combine like terms: -6.3 + 5.04 = -1.26 0.3x = -1.26 Divide each side by '0.3'. x = -4.2 Simplifying x = -4.2
| f(f(x))=25x+9 | | H(t)=-16t^2+72t+5 | | 4/3(pi)10^3 | | 5y=0-10 | | x^2-10x-25=21-25 | | -38=5(2y-1) | | x+0.5=3.2 | | 0-10=5y | | -6/5x=-7 | | 1-cos(6x)=3cos(2x) | | 1/6t=4 | | Y=sin(4x) | | (-2/3)x^2-5 | | 5x^2+13-6=0 | | 10h+5=85 | | 19z-6(4z-1)= | | 20x^2+5.2x-0.5=0 | | 0=8-2y | | 6=2.5(w-2) | | 20x^2=1 | | 6(-6n+5)=138 | | 2r+55=6r+72r | | 8m-15=33 | | 7x+24=14 | | 13=-x/5 | | t-4=15 | | 6y=4x+7 | | y=1.5+3 | | 7(7x+8)+8= | | -51/2m=-22 | | 7z-z=-6z-3-6z | | ((sqrt(x-3))/(x-3))=0 |